2019
DOI: 10.3390/nu11071668
|View full text |Cite
|
Sign up to set email alerts
|

Can Nutritional Intervention for Obesity and Comorbidities Slow Down Age-Related Hearing Impairment?

Abstract: Background: Age-related hearing impairment (ARHI), the most common sensory deficit in the elderly, is associated with enormous social and public health burdens. Emerging evidence has suggested that obesity and comorbidities might increase the risk of ARHI. However, no reviews have been published that address the role of nutritional interventions for obesity and comorbidities in the prevention of ARHI. Methods: A PubMed database search was conducted to identify the relationship between obesity and ARHI. “Obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Furthermore, it has been found that hearing loss causes an increase in oxidative stress, an increase in the inflammatory state, sedentary lifestyle, and lack of physical activity [28]. The participation of intermediary factors should also be mentioned, such as atherosclerosis, which can be found in hypertension and reduce blood flow to the cochlea by hardening or constricting the internal auditory artery [29].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Furthermore, it has been found that hearing loss causes an increase in oxidative stress, an increase in the inflammatory state, sedentary lifestyle, and lack of physical activity [28]. The participation of intermediary factors should also be mentioned, such as atherosclerosis, which can be found in hypertension and reduce blood flow to the cochlea by hardening or constricting the internal auditory artery [29].…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Postmitotic HCs and SGNs are particularly susceptible to noise exposure, ototoxic substances, and oxidative damage. Blood vessels in the stria vascularis deliver nutrients such as oxygen and glucose to the cochlea [87] . The microcirculation of the cochlea includes that of the cochlear spiral organ region, stria vascularis, and vestibular organs.…”
Section: Cochlear Microcirculation and Inflammationmentioning
confidence: 99%
“…Blood vessels in the stria vascularis deliver nutrients such as oxygen and glucose to the cochlea. [87] The microcirculation of the cochlea includes that of the cochlear spiral organ region, stria vascularis, and TA B L E 1 Differences between the BBB and BLB.…”
Section: Interactions Between Cochlear Inflammatory Response and Immu...mentioning
confidence: 99%
“…Our previous clinical cohort study highlighted the protective role of adiponectin against ARHL development [67]. The interaction between adiponectin and its type 1 receptor in the cochlea may exhibit protective effects against hair cell apoptosis [68,69]. Low-fat diets, wherein 30% or less of the calories are derived from fat, may also protect against ARHL.…”
Section: Low Fat and Low Cholesterol Dietmentioning
confidence: 99%